Cadaveric versus living-donor livers: differences in inflammatory markers after transplantation - Jassem, Wayel; Koo, Dicken D H; Cerundolo, Lucia; Rela, Mohamed; Heaton, Nigel D; Fuggle, Susan V (Transplantation, 2003)
Prolonged cold storage of organs for transplantation may lead to inflammatory damage upon reperfusion. The aim of this study was to investigate whether organs from living donors experience less damage upon reperfusion than those retrieved from cadaver donors, where cold ischemia times are significantly longer. Biopsies were obtained from cadaveric (n=23) and living-related donor (LRD) (n=10) liver transplants before and 2 hours after reperfusion. Cryosections were stained with antibodies against neutrophils, platelets, activated platelets, and endothelium. LRD liver allografts showed minimal changes postreperfusion. In contrast, after reperfusion of cadaver allografts, neutrophil infiltration was detected in 22% and increased expression of von Willebrand factor (vWF), CD41, and P-selectin in 48%, 30%, and 13% of allografts, respectively. In cadaver allografts with deposition of activated platelets expressing either P-selectin or vWF, the cold ischemia time was significantly longer (885 +/- 123 min vs. 608 +/- 214 min, P=0.04; 776.8 +/- 171 min vs. 559.3 +/- 216 min, P=0.01, respectively). Increases in neutrophils and platelets after reperfusion were not significantly associated with clinical events posttransplant. However, in cadaver transplants that experienced early acute rejection, the mean cold ischemia time was significantly longer than in allografts with no rejection (732 +/- 174 min vs. 480 +/- 221 min, P=0.006). This study demonstrates that in the clinical situation, cold ischemia causes platelet deposition and neutrophil infiltration after reperfusion of cadaveric liver allografts. These early inflammatory events may contribute to make the graft more susceptible to acute rejection.